The manipulation of strain, when stress is controlled, modulates in vivo tendon mechanical properties but not systemic TGF‐β1 levels. Issue 5 (23rd September 2013) - McMahon, Gerard E.; Morse, Christopher I.; Burden, Adrian; Winwood, Keith; Onambélé‐Pearson, Gladys L.
Abstract: Modulators of loading‐induced in vivo adaptations in muscle–tendon complex (MTC) mechanical properties remain unclear. Similarly contentious, is whether changes in MTC characteristics are associated with growth factor levels. Four groups were subjected to varying magnitudes of stress/strain: Group 1 trained with the MTC at a shortened position (MTCS; n = 10); Group 2 at a lengthened position (MTCL; n = 11; stress levels matched to MTCS); Group 3 over a wide range of motion (MTCX; n = 11); and Group 4 ( n = 10) was the control population (no training). Patella tendon Stiffness ( P < 0.001), Young's modulus, and quadriceps torque ( P < 0.05) increments (only seen in the training groups), showed MTCL and MTCX groups responses to be superior to those of MTCS ( P < 0.05). In addition, MTCL and MTCX better maintained adaptations compared to MTCS ( P < 0.05) following detraining, with a pattern of slower loss of improvements at the early phase of detraining in all training groups. There were no significant changes ( P > 0.05) in antagonist cocontraction, patella tendon dimensions or circulating transforming growth factor beta (TGF‐β1) levels following training or detraining in any of the groups. We conclude that chronically loading the MTC in a relatively lengthened position (which involves greater strains) enhances its mechanical properties, more so than loading in a shortened position. This is true even after normalizing for internal stress. The underlying endocrine mechanisms do not appear to be mediated via TGF‐β1, at least not at the systemic level. Our findings have implications with regard to the effectiveness of eccentric loading on improved tendon structural and mechanical properties. Abstract : e00091 Abstract : This study describes the manner in which tendon strain during chronic loading/unloading affects tendon dimensional and mechanical properties, as well as muscle function. We also determine the degree of association of these adaptations with a growth factor that has pleiotropic effects on muscle and tendon transforming growth factor beta (TGF‐β1). We demonstrate that the impact of strain on the muscle–tendon complex (over and above the absolute stress imposed on this unit) optimizes the magnitude of improvement in both tendon and muscular functional characteristics.